2019
DOI: 10.1186/s13071-019-3798-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of honey-baited FTA cards in combination with different mosquito traps in an area of low arbovirus prevalence

Abstract: BackgroundThe threat of mosquito-borne diseases is increasing in continental Europe as demonstrated by several autochthonous chikungunya, dengue and West Nile virus outbreaks. In Switzerland, despite the presence of competent vectors, routine surveillance of arboviruses in mosquitoes is not being carried out, mainly due to the high costs associated with the need of a constant cold chain and laborious processing of thousands of mosquitoes. An alternative approach is using honey-baited nucleic acid preserving ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 48 publications
2
34
1
Order By: Relevance
“…The detection of ISVs through metagenomics on honey-baited FTA cards provides evidence that these viruses could be transmitted within mosquitoes' expectorations, thereby contradicting previous beliefs that they could not be expelled with saliva [19]. Our findings are supported by the tissue tropism evidenced for Culex flavivirus (family Flaviviridae) and Phasi Charoen-like virus (PCLV) (genus Phasivirus, family Phenuiviridae), as they were also detected in salivary glands of Cx.…”
Section: Overall Remarks Of the Approach And Future Perspectivescontrasting
confidence: 63%
See 2 more Smart Citations
“…The detection of ISVs through metagenomics on honey-baited FTA cards provides evidence that these viruses could be transmitted within mosquitoes' expectorations, thereby contradicting previous beliefs that they could not be expelled with saliva [19]. Our findings are supported by the tissue tropism evidenced for Culex flavivirus (family Flaviviridae) and Phasi Charoen-like virus (PCLV) (genus Phasivirus, family Phenuiviridae), as they were also detected in salivary glands of Cx.…”
Section: Overall Remarks Of the Approach And Future Perspectivescontrasting
confidence: 63%
“…Furthermore, to improve the sensitivity and efficiency of our approach, honey-baited FTA cards could be placed inside Box gravid traps, as a recent study conducted in Switzerland demonstrated these to be the most effective traps for capturing females of different species when searching for an ovipositional site. In addition, these traps also exhibited the highest feeding success on honey-baited FTA cards [19].…”
Section: Overall Remarks Of the Approach And Future Perspectivesmentioning
confidence: 95%
See 1 more Smart Citation
“…Subsequently, 258 human cerebrospinal fluid samples collected between 2015 and 2017 for routine clinical care in a tertiary level hospital in Geneva were tested for USUV by RT-PCR, but no samples tested positive [ 104 ]. In 2011 and 2012, USUV was found in mosquitoes from Ticino [ 105 ], and recently confirmed in the same area [ 106 ]. USUV-positive mosquito pool of Cx.pipiens / Cx.…”
Section: Switzerlandmentioning
confidence: 76%
“…The current strategy to prevent and control Aedes-borne diseases in Canton Ticino is based on the surveillance and reports of human cases and the fight against the A e . albopictus mosquito [ 19 ]. Until now, no autochthonous cases of disease have been reported from Ticino or elsewhere in Switzerland.…”
Section: Introductionmentioning
confidence: 99%